2018
DOI: 10.1111/dom.13273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alirocumab on lipids and lipoproteins in individuals with metabolic syndrome without diabetes: Pooled data from 10 phase 3 trials

Abstract: AimsThis analysis assessed the efficacy and safety of alirocumab, a proprotein convertase subtilisin/kexin type 9 inhibitor, in patients with or without metabolic syndrome (MetS) using pooled data from 10 phase 3 ODYSSEY trials.Materials and MethodsData from 4983 randomized patients (1940 with MetS; 1642 with diabetes excluded) were assessed in subgroups by MetS status. Efficacy data were analysed in 4 pools per study design: 2 placebo‐controlled pools (1 using alirocumab 150 mg every 2 weeks [Q2W], 1 using 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
1
5
1
2
Order By: Relevance
“…We could only detect a modest, non-significant reduction in fasting plasma triglycerides of 10%. This result is consistent with findings of a large, pooled analysis of 10 phase III alirocumab trials with 4983 participants, also reporting a modest triglyceride reduction of approximately 15% [ 33 ]. The pooled analysis also suggested that the triglyceride-lowering effect of alirocumab treatment is independent of a metabolic syndrome.…”
Section: Discussionsupporting
confidence: 91%
“…We could only detect a modest, non-significant reduction in fasting plasma triglycerides of 10%. This result is consistent with findings of a large, pooled analysis of 10 phase III alirocumab trials with 4983 participants, also reporting a modest triglyceride reduction of approximately 15% [ 33 ]. The pooled analysis also suggested that the triglyceride-lowering effect of alirocumab treatment is independent of a metabolic syndrome.…”
Section: Discussionsupporting
confidence: 91%
“…68 Targeting PCSK9 has emerged as a novel approach to treat hypercholesterolemia. [69][70][71][72][73] Other potential novel therapies are heparin mimetics. Heparin and related compounds are known to lower plasma TG concentrations by releasing lipoprotein lipase into plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Henry et al found a significant reduction in apolipoprotein B (40%‐50% reduction with statins) and similar reductions on non‐HDLs with PCSK9 inhibitors. There were no significant differences between patients with or without metabolic syndrome …”
Section: Introductionmentioning
confidence: 88%
“…There were no significant differences between patients with or without metabolic syndrome. 4 In summary, the use of PCSK9 inhibitors in patients with cardiometabolic conditions has impressive benefits. In intolerant statins, patients frequently benefit from these compounds, but the cost is high.…”
mentioning
confidence: 99%